Analisis Fatwa Dewan Syariah Majelis Ulama Indonesia Tentang Akad Bagi Investor Emas Melalui Platform Aplikasi Bareksa - Sunarsa, Sasa; Ramdani, Moh Nurkholis (STAI Al Musaddadiyah Garut, 2023)
Investment is an activity that aims to develop assets, besides that it is also a commitment to a certain amount of money as well as other resources that are carried out at the present time with the aim of obtaining a number of benefits in the future. The formulation of the problem in this research is 1). What is the view of the fatwa of the Ulama in investing in gold through digital media? 2). What is the sale and purchase contract used to invest in digital gold through the Bareksa application platform? The purpose of this study is to find out the views of Muslim scholars on investing in gold through digital media and the types of contracts used in investing in gold through the Bareksa application platform. The author uses a research library research with the use of descriptive methods. The results of this study are based on the DSN-MUI Fatwa decision regarding buying and selling gold in cash, namely the law of buying and selling gold in cash, either through buying and selling in general or buying and selling with a murabaha contract, then the law is permissible (jaiz, mubah) , and the contract used in the practice of buying and selling is a murabahah contract while in the safekeeping of goods it uses a wadiah yad Al-Amanah contract. Keywords: Investment, Akad, Ulama Fatwa